Raman Effect on the Polarization State in Low-Birefringence Fiber (Journal of Atomic and Molecular Sciences, 2021)
In low birefringence fiber, by solving the coupled nonlinear Schrodingerequations contained the Raman effect for satisfy right- and left-handed circularly polarizedlight in the quasi-CW case, the relationship between the effective polarizationbeat length and changes of input power have been studied emphatically in low- andhigh input power situation considering the Raman effect or not. The results showedthat the polarization state evolution cycles of the incident light can be changed andmeanwhile the transmission distance of the incident light also can be changed due toRaman effect, regardless of the polarization of the incident light was along the slowaxis or along the fast axis.